USABILITY AND USEFULNESS FOR ONLINE SINGLE SUBMISSION SYSTEM IN INVESTMENT AND ONE-STOP INTEGRATED SERVICE OFFICE, SAMARINDA CITY - Ummul Hairah; Edy Budiman (Journal of Information Technology and Its Utilization, 2021)
The challenge of implementing the online service public system from the user side of the system is the acceptance and use of technology. User characteristics for accepting or rejecting the use of the system for various reasons (digital literacy) for the adoption of new technologies such as the Online Single Submission (OSS) system. The research purpose is to offer a theoretical model of the Technology Acceptance Model (TAM) to evaluate the use and acceptance of users to the OSS system at the Investment Service and One-Stop Integrated Service of the Samarinda City during the Covid-19 pandemic. The method used to measure the variable effects using Partial Least Square - Structural Equation Modeling (PLS-SEM) on perceived ease of use (usability) and perceived usefulness, behavior intention to use, and Attitude toward Using the Online Single Submission system. Based on the results of testing the hypothesis H0 proposed is accepted. OSS system users find it useful to assist in completing work (licensing process). That perceived Ease of Use, Perceived Usefulness have a positive effect and significant on the Behaviour Intention to Use adopt the OSS system for users and have a goodness of fit.